Which is the most suitable local anaesthetic when inferior nerve blocks are used for impacted mandibular third molar extraction? A network meta-analysis. Issue 11 (November 2020) - Camps-Font, O.; Figueiredo, R.; Sánchez-Torres, A.; Clé-Ovejero, A.; Coulthard, P.; Gay-Escoda, C.; Valmaseda-Castellón, E.
Abstract: The aim of this study was to compare the efficacy and safety of the different local anaesthetic agents for the extraction of impacted lower third molars. A network meta-analysis was performed of all published reports of randomized controlled clinical trials assessing efficacy (anaesthetic success and absence of need for supplementary anaesthesia during the surgical procedure) and/or safety (number of adverse events) of anaesthetic agents. Three electronic databases were searched, from their earliest records up to April 2019. Additionally, the grey literature was searched to identify further potential candidates for inclusion. Anaesthesia had to be delivered by an inferior alveolar nerve block, complemented with infiltration anaesthesia of the buccal nerve. The quality of the studies was assessed using the Cochrane Collaboration tool. This study included a total of 21 trials (2021 molars) assessing the efficacy and 19 trials (1977 molars) assessing the safety of 11 anaesthetic solutions. Seven of the studies included were considered to have a high risk of bias. The most effective local anaesthetic for the extraction of impacted mandibular third molars appeared to be 4% articaine, with significant differences when compared with 2% lidocaine, 0.5% bupivacaine, and 1% ropivacaine. Lidocaine is the safest local anaesthetic, although all investigated solutions can be used safely.